2022
DOI: 10.1038/s41598-022-18906-1
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 can infect human embryos

Abstract: The spread of SARS-CoV-2 has led to a devastating pandemic, with infections resulting in a range of symptoms collectively known as COVID-19. The full repertoire of human tissues and organs susceptible to infection is an area of active investigation, and some studies have implicated the reproductive system. The effects of COVID-19 on human reproduction remain poorly understood, and particularly the impact on early embryogenesis and establishment of a pregnancy are not known. In this work, we explore the suscept… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Infection was most common in totally hatched blastocysts. Infected cells had signs of cell degeneration suggesting cytopathic effects of infection ( Montano et al , 2022 ). Studies evaluating the impact of COVID-19 on embryo developmental potential and ART outcomes are discussed in the next section.…”
Section: Resultsmentioning
confidence: 99%
“…Infection was most common in totally hatched blastocysts. Infected cells had signs of cell degeneration suggesting cytopathic effects of infection ( Montano et al , 2022 ). Studies evaluating the impact of COVID-19 on embryo developmental potential and ART outcomes are discussed in the next section.…”
Section: Resultsmentioning
confidence: 99%
“…In the ovary, ACE2 plays a vital role in the regulation of steroidogenesis, follicle development and oocyte maturation ( 10 , 11 ), and is also required for endometrial stromal decidualization ( 12 ). Additionally, in vitro experiments have proven a cytopathic effect of SARS-CoV-2 on human blastocyst, ranging from focal degradation to global collapse ( 13 ). These findings suggest that SARS-CoV-2 infection may negatively affect female fertility and the outcomes of assisted reproductive treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Another study utilizing donated human gametes evaluated the expression of SARS-CoV-2 receptor protein on embryos and found that the 5th-and 7th-day blastocysts showed the expression of ACE2 and BSG on the trophoblast and inner cell mass cell membrane, suggesting that SARS-CoV-2 could potentially infect embryos [22]. When human blastocysts are exposed to SARS-CoV-2, both trophoblast cells and inner cell mass cells are infected, displaying signs of cellular degeneration, indicating the pathogenic effect of infection [23]. The zonal pellucida seems to have a protective effect against SARS-CoV-2 infection [23].…”
Section: Discussionmentioning
confidence: 99%